Defiant desire : some dialectical legacies of D.H. Lawrence - Widmer, Kingsley, 1925-2009. (Carbondale, Ill. : Southern Illinois University Press, 1992)
Kingsley Widmer, one of the more insightful and provocative learned critics, has had a considerable influence on D.H. Lawrence studies. Here he elaborates his crucial argument that the erotic conversion experience and its dialectic of social negation centrally define Lawrence and create his major legacies. In dialectically considering all of Lawrence's novels and many of his essays and stories, Widmer carries the issues beyond the texts to Lawrence's literary and ideological inheritors, including Henry Miller, Norman Mailer, and a variety of others. In addition, he imbeds Lawrence's fictions and roles in the "dark prophecy" of affirmatively countering the Nietzschean tradition and, in a striking chapter on Lady Chatterley's Lover, explores the use of obscenity, sexual ideology, and anticlass utopianism. Finally, Widmer boldly ranges over Lawrence's blasphemous relation to censorship, to feminist/masculinist disputes, and to deconstructionist and certain sexual ideologies. This is Lawrence as a major dissident culture hero with a still pertinent, drastic revisionism of human responses in a nihilistic world. It is a large and controversial critical view.
Includes bibliographical references (pages 222-238) and index.
Electronic reproduction.
Master and use copy. Digital master created according to Benchmark for Faithful Digital Reproductions of Monographs and Serials, Version 1. Digital Library Federation, December 2002.
digitized
Print version record.
English.
Keywords: Lawrence, D. H. -- 1885-1930 -- Criticism and interpretation; Nietzsche, Friedrich Wilhelm, -- 1844-1900 -- Influence; Lawrence, D. H. -- 1885-1930; Nietzsche, Friedrich Wilhelm, -- 1844-1900; Lawrence, David H; Negativity (Philosophy) in literature; English fiction -- German influences; Negation (Logic) in literature; Desire in literature; Dialectic; Négativité (Philosophie) dans la littérature.; Négation (Logique) dans la littérature.; Désir dans la littérature.; Dialectique; dialectic; LITERARY CRITICISM -- European -- English, Irish, Scottish, Welsh; Desire in literature; Dialectic; English fiction -- German influences; Influence (Literary, artistic, etc.); Negation (Logic) in literature; Negativity (Philosophy) in literature; Sexualität; Literatur; Rezeption; Geschichte; Erotik; Aufsatzsammlung; USA; English; Languages & Literatures; English Literature; Criticism, interpretation, etc